2016
DOI: 10.1002/14651858.cd002118.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage stage versus blastocyst stage embryo transfer in assisted reproductive technology

Abstract: Cleavage stage versus blastocyst stage embryo transfer in assisted reproductive technology. Cochrane Database of Systematic Reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
178
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(213 citation statements)
references
References 95 publications
17
178
3
1
Order By: Relevance
“…A recent metaanalysis showed that there is a small advantage in performing blastocyst transfer compared to cleavage stage transfer when considering the live birth rates. However, these results were observed only in good prognosis patients and the cumulative clinical pregnancy rates were higher for cleavage stage transfer when compared to blastocyst transfer [28]. In our IVF center the cleavage stage embryo transfer was a routine procedure in the study period.…”
Section: Discussionmentioning
confidence: 86%
“…A recent metaanalysis showed that there is a small advantage in performing blastocyst transfer compared to cleavage stage transfer when considering the live birth rates. However, these results were observed only in good prognosis patients and the cumulative clinical pregnancy rates were higher for cleavage stage transfer when compared to blastocyst transfer [28]. In our IVF center the cleavage stage embryo transfer was a routine procedure in the study period.…”
Section: Discussionmentioning
confidence: 86%
“…The recent literature on blastocyst transfers supports an improved pregnancy rate as opposed to cycle day 3 transfers [35,36]. A move of all transfers to blastocyst-stage embryos will also improve the live birth rates per transfer by removing from the denominator the cases failing to reach blastocyst stage embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Others have stagnated as the discourse continues over single or sequential media [5,6], compositional variants, and their influence on gene expression patterns in media comparisons [7]. In the end, even the question of what stage to transfer-cleavage or blastocyst-lingers while properly executed RCTs loom in a background of mediocrity in terms of clinical decision making [8].…”
Section: Commentarymentioning
confidence: 99%